ANALISIS SISTEM DISTRIBUSI DAN INSTALASI LISTRIK PT. AEROFOOD ACS BALIKPAPAN - anwar fattah; janjang Febry Dian samudra; bambang sugeng (Lembaga Penelitian Universitas Balikpapan, 2019)
Electric power is an absolute thing that needed in service industry like catering because too many tools that needs electric power to move on. Electric power is not only gives benefit but also can danger and damage the human being. Therefore making electric instalation is have to do well in accordance with the procedure and the rules, until the electric instalation can be functioned save for human being and construction and economic value. Discuss about distribution and instalation system in PT. Aerofood ACS Balikpapan which needs continuous electric supply until all activities on the company are not disturbed. Distribution system in PT. Aerofood ACS Balikpapan is using radial system. Where the main source of electricity supplied by PLN and if at any time PLN dead then use the generator set as backup. From the analysis obtained, that in the stress system at PT. Aerofood ACS Balikpapan experienced a shrinkage of voltage, but the change of voltage shrinkage is still within the tolerance range allowed by PUIL 2000 ± 5 % so we can say that condition of drop voltage system are good. From the analysis, all the connected cabel in PT. Aerofood ACS Balikpapan are good and safe to use. But there are some of MCCB or MCB and grounding system which not suitable with PUIL. Totally distribution and installation system in Hotel Gran Mahakam, South Jakarta are not safe and good enough to use. However, for the system breaker power and grounding system some of which are not in accordance with PUIL 2000. So as a whole system of distribution and installation at PT. Aerofood ACS Balikpapan can not be said safe and good to use.